D. I . Zaitsev (Algebra and Discrete Mathematics, 2012)
In the spring of 2012, the 70th birthday of Dmitriy I. Zaitsev (1942-1990) will come. D.I Zaitsev did not live two years to his 50th birthday, but his life in mathematics will be long. His main interests were very wide; they spread over all areas of modern group theory. His work greatly influenced the development of the infinite group theory. Many of his results have already become classical and have been included in monographs and surveys. The methods developed by him found numerous followers who have successfully applied them.